Restriction Site-Associated DNA Sequencing Reveals Local Adaptation Despite High Levels of Gene Flow in Sardinella lemuru (Bleeker, 1853) Along the Northern Coast of Mindanao, Philippines - Labrador, Kevin; Palermo, Joseph Dominic; Agmata, Altair; Ravago-Gotanco, Rachel; Pante, Ma. Josefa (Frontiers in Marine Science, 2022)
Stock identification and delineation are important in the management and conservation of marine resources. These were highlighted as priority research areas for Bali sardinella (Sardinella lemuru) which is among the most commercially important fishery resources in the Philippines. Previous studies have already assessed the stocks of S. lemuru between Northern Mindanao Region (NMR) and Northern Zamboanga Peninsula (NZP), yielding conflicting results. Phenotypic variation suggests distinct stocks between the two regions, while mitochondrial DNA did not detect evidence of genetic differentiation for this high gene flow species. This paper tested the hypothesis of regional structuring using genome-wide single nucleotide polymorphisms (SNPs) acquired through restriction site-associated DNA sequencing (RADseq). We examined patterns of population genomic structure using a full panel of 3,573 loci, which was then partitioned into a neutral panel of 3,348 loci and an outlier panel of 31 loci. Similar inferences were obtained from the full and neutral panels, which were contrary to the inferences from the outlier panel. While the full and neutral panels suggested a panmictic population (global FST ∼ 0, p > 0.05), the outlier panel revealed genetic differentiation between the two regions (global FST = 0.161, p = 0.001; FCT = 0.263, p < 0.05). This indicated that while gene flow is apparent, selective forces due to environmental heterogeneity between the two regions play a role in maintaining adaptive variation. Annotation of the outlier loci returned five genes that were mostly involved in organismal development. Meanwhile, three unannotated loci had allele frequencies that correlated with sea surface temperature. Overall, our results provided support for local adaptation despite high levels of gene flow in S. lemuru. Management therefore should not only focus on demographic parameters (e.g., stock size and catch volume), but also consider the preservation of adaptive variation.